ENVIRONMENTAL INFLUENCE ON THE MIGRATION AND SETTLEMENT OF OYO-OSUN COCOA MIGRANT FARMERS IN ONDO DIVISION, SOUTHWESTERN NIGERIA, 1930s-1970s - Adesote Samson Adesola (Romanian Journal of Historical Studies)
The main thrust of this paper is to critically interrogate the nexus between environmental influence and migrant settlement. It argues that the place of environmental influence on population movement whether forced or voluntary cannot be overemphasized. It specifically discusses how environmental factor constituted one of the major factors that contributed to the migration and settlement of Oyo-Osun cocoa migrant farmers in Ondo Division of Southwestern Nigeria between 1930s and 1970s. Environmental influence is seen in this paper as a major push and pull factor of internal migration. While environmental challenge faced by the Oyo-Osun cocoa migrant farmers was a major push factor that forced them to leave their different places of origin, the favourable climatic conditions in Ondo Division for the cultivation of cocoa such as fertile land, availability and accessibility to abundant land as well as liberal reception of indigenes constituted pull factor, which attracted them to the division during this period. It explains that Ondo Division was one of the major divisions in Ondo Province that attracted large number of cocoa migrant farmers from other parts of Southwestern Nigeria between 1930s and 1970s. This development was as a result of favourable environment for cocoa plantation. It concludes that the emigration of these cocoa migrant farmers led to the emergence of different migrant settlements in the division such as Ago-Ikirun, Sokoto, Labosipo, Bamikemo-Oja among others. The paper is based on Everett Lee push and pull theory of migration. The methodological approach adopted in this paper is historical, thematic and qualitative. Sources of information include primary and secondary materials derived from archives, oral interviews and extant literature.